Amine‐Free Reversible Hydrogen Storage in Formate Salts Catalyzed by Ruthenium Pincer Complex without pH Control or Solvent Change. Issue 8 (30th March 2015) - Kothandaraman, Jotheeswari; Czaun, Miklos; Goeppert, Alain; Haiges, Ralf; Jones, John‐Paul; May, Robert B.; Prakash, G. K. Surya; Olah, George A.
Abstract: Due to the intermittent nature of most renewable energy sources, such as solar and wind, energy storage is increasingly required. Since electricity is difficult to store, hydrogen obtained by electrochemical water splitting has been proposed as an energy carrier. However, the handling and transportation of hydrogen in large quantities is in itself a challenge. We therefore present here a method for hydrogen storage based on a CO2 (HCO3 − )/H2 and formate equilibrium. This amine‐free and efficient reversible system (>90 % yield in both directions) is catalyzed by well‐defined and commercially available Ru pincer complexes. The formate dehydrogenation was triggered by simple pressure swing without requiring external pH control or the change of either the solvent or the catalyst. Up to six hydrogenation–dehydrogenation cycles were performed and the catalyst performance remained steady with high selectivity (CO free H2 /CO2 mixture was produced). Abstract : Carbon‐neutral cycle! A practical, reversible, and amine‐free hydrogen‐storage system using Ru‐pincer catalyst is presented here. At high H2 pressure, hydrogen combined with CO2 (HCO3 − ) is stored in the form of formate salts. At low pressure, H2 is released. Up to six hydrogenation–dehydrogenation cycles were performed and the catalyst performance remained steady with high selectivity.